AUTOMATION OF THE WORK OF GREENHOUSES - Pirnazarov Ilxom Islamovich; Karimov Tashmukhamed Khalmukhamedovich; Gulboyev Sardor Baxtiyor o`g`li (Web of Journals Publishing, 2025)
This article covers modern methods of management of greenhouses based on IMRAT (Scientific, Monitoring, Resource Management, Automation and Technology) requirements. The article discusses the scientific approach, real-time monitoring, rational use of resources, the importance of using automation systems and modern technologies for the effective organization of greenhouse activity.
Keywords: Technology, communications, resource, IMRAT, automation, monitoring.